Three dimensional memristor-based neuromorphic computing system and its application to cloud robotics. (October 2017) - An, Hongyu; Li, Jialing; Li, Ying; Fu, Xin; Yi, Yang
Highlights: A novel Neuromorphic Cloud Robotics (NC-Robotics) system is proposed by replacing conventional CPUs based on Von Neumann architecture with three-dimensional neuromorphic integrated circuits (3D-NCs). A novel 3D-NCs architecture combining vertical RRAM structure is investigated and its concise equivalent circuit model is created, evaluated and analyzed through SPICE simulations. An Analog-to-Spiking Converter (ASC) design is introduced, which can convert analog signal to spiking signal sequences for further processing in neuromorphic computing chips. Abstract: Neuromorphic computing based on three-dimensional inetgraed circuits (3D-NCs) offers a novel hardware implementation of neuromorphic computing, and provides high device density, massively parallel signal processing capability, low power consumption, and direct analog signal processing capability. In this paper, by replacing conventional CPUs based on Von Neumann architecture with 3D-NCs, a novel neuromorphic computing based cloud robotics (NC-robotics) system is proposed, which is constructed by 1) cloud server center using 3D-NCs as computing units, 2) neuromorphic robotics based on neural network control technology. Besides the benefits of normal Cloud Robotics platform, this NC- Robotics system has more advantages on massive parallel-computing, analog signals processing, and lower power consumption. In order to implement this NC––Robotics system, a novel 3D-NCs architecture combining vertical RRAM structure is investigated and its concise equivalent circuit model is created, evaluated, and analyzed through SPICE simulations.